2018
DOI: 10.1016/j.ijdevneu.2018.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Gene analysis: A rare gene disease of intellectual deficiency‐Cohen syndrome

Abstract: Cohen syndrome is a rare, genetic, connective-tissue disorder, which is caused by mutations in the gene COH1 (VPS13B, Vacuolar Protein Sorting 13 Homolog B) at the chromosome 8q22. The disease is rare reported, which major clinical features include postnatal microcephaly, obesity, short stature, intellectual disability, progressive retinal dystrophy, intermittent neutropenia and many other unusual facial feature. We report four patients in China who were diagnosed with Cohen syndrome by genetic testing and cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…Founder mutations have been described in several areas [2]. Only a few VPS13B mutations have been reported sporadically in patients with CS (two definitive CS and three probable CS) in the Chinese population [8–10]. In the present study, exome sequencing identified two novel VPS13B mutations in a Chinese family with two offspring–patients affected by CS and hyperlinear palms.…”
Section: Introductionmentioning
confidence: 52%
See 1 more Smart Citation
“…Founder mutations have been described in several areas [2]. Only a few VPS13B mutations have been reported sporadically in patients with CS (two definitive CS and three probable CS) in the Chinese population [8–10]. In the present study, exome sequencing identified two novel VPS13B mutations in a Chinese family with two offspring–patients affected by CS and hyperlinear palms.…”
Section: Introductionmentioning
confidence: 52%
“…Hyperlinear palms have been reported among FLG -mutated patients [14] with atopic dermatitis or ichthyosis vulgaris [15]. We tried contacting VPS13B -mutated Chinese patients [8–10] to see if they have hyperlinear palms as a means of verifying if hyperlinear palms are a component phenotype of CS. However, we have not received any response from these patients.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, a pattern of agalactosylated and asialo‐fucosylated structures, indicative of a N‐glycan maturation defect, was found in serum proteins of these patients . Intermittent congenital neutropenia is a hallmark of this disease (detected in 168/224 VPS13B‐CDG patients) . One patient had leukopenia without neutropenia while another had pancytopenia .…”
Section: The Immunological Impact Of Glycosylation Defects—an Update mentioning
confidence: 94%
“…Here, we reviewed all the patients with CS con rmed by gene examinations in China (Table 1) and analyzed the gene variant sites and clinical features. It was found that 5 of 12 patients (including current case) carried c.6940+1G>T variant of VPS13B gene [20][21][22]. Only this patient was homozygous, and the other 4 cases were heterozygous variation.…”
Section: Discussionmentioning
confidence: 99%
“…It is obvious that the variant frequency of East Asian population is higher than other populations, and there is little reports about this variation in other populations [23][24][25][26][27][28]. The c.6940+1G>T variation was rst discovered by Chinese doctor in 2016, and has been reported four times in China in recent years [20][21][22]. This patient is the fth case but the rst homozygous variation patient in China.…”
Section: Discussionmentioning
confidence: 99%